2020
DOI: 10.1021/acs.molpharmaceut.0c00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Common Excipients on Intestinal Drug Absorption in Wistar Rats

Abstract: The aim of the present paper is to study the effect of common excipients on the permeability of atenolol (as drug absorbed mainly by passive diffusion) and rhodamine (as P-glycoprotein substrate). The apparent permeability was measured by an in situ perfusion method in Wistar rats using the closed loop Doluisio’s method. Permeability values were characterized in the absence and presence of 18 commonly used excipients. Excipient concentrations were selected based on the amounts in oral immediate release dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The impact of excipients on the pharmacokinetics of BCS1/3 drugs is a subject which has caused much controversy in the literature, with advocates on one side of the debate some pointing to data where small changes in excipient levels were correlated with PK change in human BE studies 29,30,56 , data from cell line measurements [57][58][59][60][61] or in-situ animal perfusion studies 57,62 where excipients have altered drug permeability as evidence that even small changes in excipient levels can lead to inequivalence.…”
Section: Be Failures Related To Small Changes In Excipient Levelsmentioning
confidence: 99%
“…The impact of excipients on the pharmacokinetics of BCS1/3 drugs is a subject which has caused much controversy in the literature, with advocates on one side of the debate some pointing to data where small changes in excipient levels were correlated with PK change in human BE studies 29,30,56 , data from cell line measurements [57][58][59][60][61] or in-situ animal perfusion studies 57,62 where excipients have altered drug permeability as evidence that even small changes in excipient levels can lead to inequivalence.…”
Section: Be Failures Related To Small Changes In Excipient Levelsmentioning
confidence: 99%
“…In addition, the relative contribution and specific effects of food components (lipids, proteins, carbohydrates) need to be investigated further . Other considerations include possible inhibitory effects on intestinal permeability, enzymes, or transporters (e.g., CYP3A4, OATP2B1, Pgp, BCRP), increased splanchnic blood flow, and gut microbiome interaction with micellar structures. ,,, Recent research has demonstrated the effect of several excipients and food additives on the inhibition of uptake and efflux transporters in the gut, especially of OAT12B1 and Pgp, in vitro , in situ , or in animal species. Other studies have shown that bacterial metabolism from gut microbiota could counterbalance this effect by metabolizing susceptible excipients to inactive metabolites . At the same time, some excipients have been found capable of enhancing drug permeation across the enterocyte apical membrane in vitro .…”
Section: Knowledge Gaps Challenges and Limitationsmentioning
confidence: 99%
“…According to the International Coordination Committee for the Registration of Pharmaceutical Products for Human Use (ICH) guidelines and the M9 Bioequivalence Exemptions Based on the Biopharmaceutical Classification System [1][2][3][4] permeability is closely related to the rate and extent of drug absorption in the body and is one of the key factors in the transport of drugs in the body through expanded membranes and is relevant to drug development. Pharmaceutical excipients are non-physiologically active substances in pharmaceuticals that affect their absorption and bioavailability in the body [5][6][7]. For poorly permeable drugs, permeation enhancers are commonly used [8][9][10][11], for example, fatty alcohols, which increase drug permeability by altering the structure and properties of biofilms.…”
Section: Introductionmentioning
confidence: 99%